Impacto da PolÃtica de Reserva de Vagas nas taxas de EvasÃ£o na Unesp - Massini-cagliari, Gladis [UNESP]; Lemke, Ney [UNESP]; Barreiro, Iraãde Marques De Freitas [UNESP]; Domingues, Maria Aparecida Custã³dio [UNESP]; Putti, Fernando Ferrari [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (PublicaÃ§Ã£o da Rede de AvaliaÃ§Ã£o Institucional da EducaÃ§Ã£o Superior (RAIES), da Universidade Estadual de Campinas (UNICAMP) e da Universidade de Sorocaba (UNISO)., 2021)
Student dropout is a topic of worldwide interest in the field of education research; however, current understanding of the phenomenon remains insufficient, particularly when the objective is to evaluate effective retention policies. The annual dropout rate at UNESP was evaluated based on the admission selection policy. There are three admission categories: the universal exam system; a selection quota for students who studied in public schools; and a selection quota for students who are Black, Brown or Indigenous. The data was classified by course and admittance year. UNESP has campuses in 24 towns, divided into 34 campuses that provide 136 different undergraduate courses. Admission to these courses is conducted by an entrance exam with 186 different options in 63 careers. A comparison of dropout rates shows that these may depend on the admission category, but it varies over time and depends on the course subject. The data also reveal a consistent decrease in the annual dropout rates, according to the admission category.

A evasão Ã© um tema de interesse mundial na área da educação, contudo o entendimento atual sobre o fenômeno Ã© ainda insuficiente, sobretudo quando o objetivo Ã© avaliar polÃticas efetivas de evasão. Neste artigo o percentual anual de evasão da Unesp Ã© avaliado com base na adoção da polÃtica de reserva de vagas. Existem três possibilidades de ingresso - sistema universal (SU), quota por ter estudado em escola pública (EP) e quota por ser PPI (pretos, pardos, indÃgenas). Os dados foram segmentados por curso e ano de ingresso. A Unesp tem campus em 24 cidades, que reúnem 34 unidades e abrigam 136 diferentes cursos de Graduação. O ingresso para estes cursos Ã© realizado por meio de vestibular com 186 diferentes opções em 63 carreiras. Uma comparação das taxas de evasão permite observar que elas podem depender do modo de ingresso, mas isso ocorre de forma variada ao longo do tempo e depende da área do curso, não sendo significativo. Verificou-se um decréscimo consistente da taxa de evasão global e por categoria de ingresso.
Impact of the vacancy reservation policy on Unesp dropout rate
Keywords: Higher education; School dropout; Vacancy reserve policy; Educação superior; Evasão; Reserva de vagas